VITREORETINAL SURGICAL OUTCOMES PERFORMED BY SUPERVISED RETINAL FELLOWS VERSUS ATTENDING FACULTY SURGEONS. Issue 5 (May 2016) - Mason, John O.; Mason, Lauren B.; Patel, Shyam A.; McGwin, Gerald; Finley, Thomas A.; Friedman, Duncan A.; Pomerleau, Dustin L.; Albert, Michael A.; Feist, Richard M.; Thomley, Martin L.; Mason, John O.
Abstract : Purpose: To evaluate common vitreoretinal surgeries performed by retinal fellows under direct faculty supervision, compared with experienced faculty members. Methods: Retrospective study analyzing 592 consecutive eyes undergoing retinal surgery from 2009 to 2011 at Retina Consultants of Alabama/University of Alabama at Birmingham, Department of Ophthalmology. Vitreoretinal surgeries included macular hole, macular pucker, retinal detachment, diabetic vitreous hemorrhage, and diabetic tractional retinal detachment. Three fellows performed 390 cases (divided into first or second year fellows), while 4 faculty members performed 202 cases. All 390 fellow-performed cases were under direct supervision. Chi-square analysis was used to compare outcomes. Results: There were no baseline differences between the groups. The mean postoperative visual improvement was statistically significant and equal in all groups, as well as between each physician ( P ⩽ 0.0001). Complications occurred in 29/592 cases (4.8%), whereas reoperations occurred in 21/592 cases (3.5%) and were equally distributed across groups. There were no differences in complications and reoperations when comparing first-year with second-year fellows. Conclusion: With proper supervision, vitreoretinal fellows can achieve an equally high visual improvement with low complication and reoperation rates compared with experienced faculty. The year of fellowship does not significantly influence outcomes or complications. Quality outcomes after vitreoretinal surgery can be obtained throughout fellowship training. Abstract : Visual outcomes, complication rates, and reoperation rates between supervised fellow and attending-performed vitreoretinal surgeries showed no significant differences. The year of fellowship did not significantly influence reoperation and complication rates.